The Association Between Degree of Severity and Number of Medications with Quality of Life in Parkinson's Disease Patients - Heidiyana, Marisa; Surbakti, Khairul Putra; Hutagalung, Haflin Soraya (CoinReads Media Prima, 2023)
Introduction: Quality of life is an important parameter to be assessed, especially in progressive chronic diseases such as patients with Parkinson's Disease (PD). Parkinson's Disease Questionnaire-39 (PDQ-39) is the most widely used measurement tool in assessing the quality of life of PD patients. In PD, a series of features can affect the quality of life including the degree of disease severity and the number of medications. The aim of this study is to determine the relationship between the severity of the disease and the number of medications with the quality of life of people with PD so that it is hoped that it can help improve the quality of life of PD patients. Method: This study used a cross-sectional design. The research subjects were PD patients at the Neurology Polyclinic at Haji Adam Malik Hospital Medan from April - November 2020 who met the inclusion criteria. Assessing the severity of the disease using the Hoehn and Yahr and measuring the quality of life using the PDQ 39. Data analysis used the Spearman correlation test for the degree of severity and the Mann- Whitney test for the number of medications. Results: Of the 47 subjects who met the inclusion criteria, most were males (68.1%), with a mean age of 64.82 ± 9.52 years old, with University graduates as the majority of education level (46.8%) and the civil servant as the majority of a profession (34.0%). Stage 2 on Hoehn and Yahr Scales is the most common severity level of disease (55.3%), and polytherapy is the majority of the number of medications (74.5%). The median value of quality of life is 35, with the lowest score being 10 and the highest score being 98. From the results of the bivariate analysis, it was found that there was a very strong, significant association between the degree of disease severity and the quality of life (p <0.001 r=0.872), and there was a significant difference between the number of medications with the quality of life of Parkinson's disease patients (p=0.041). Conclusion: There is a very strong association between the degree of severity and the quality of life of people with Parkinson's disease and there is a difference in the quality of life of PD patients between those who receive monotherapy and polytherapy so there is an effect of the number of medication given on the quality of life of Parkinson's disease patients.